Luminescent Transparent Wood. Issue 1 (23rd November 2016) - Li, Yuanyuan; Yu, Shun; Veinot, Jonathan G. C.; Linnros, Jan; Berglund, Lars; Sychugov, Ilya
Abstract : Luminescent transparent wood is prepared by combining the complementary properties of naturally grown anisotropic porous wood and luminescent quantum dots. The wood structure introduces strong diffused luminescence and waveguiding, which can potentially be exploited for optoelectronic and photovoltaic applications, such as for planar illumination sources and luminescent buildings/furniture. Images below show the transparency, haze, and luminescence of quantum dot wood.